ADAPTATION OF ROMEO AND JULIET MODEL TO DYADIC RELATION PROBLEMS - Putri Wahyudi, Ristania
Mathematics can solve various real world problems through modeling. Not only problems in the sphere science and technology, but also in the social sphere. One of them is dyadic relations problem in the field of psychology. This final project will focus on the dyadic relationship between two individuals who are involved in a romantic relationship. The modeling of the dynamics of love is adapted from the Romeo and Juliet model and will be solved using Euler’s numerical method. There are four cases that will be studied based on the quality of the relationship and how the relationship ended. Case study for the film Gone with the Wind is used as a preliminary analysis to determine the best procedure for analyzing each case. After that, simulations are carried out on each film that has been selected for each case. The results obtained are able to retell the storyline of the film such that the model used in this final project is good enough to describe the dynamics of two people’s feelings in a relationship.